2016
DOI: 10.1590/1413-81232015219.15912016
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do escopo de prática de médicos participantes do Programa Mais Médicos e fatores associados

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
23

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 13 publications
2
15
0
23
Order By: Relevance
“…A study developed with active professionals in the Programa Mais Médicos (PMM) (More Physicians Program) demonstrated that working in the geographic North region is a factor that contributes to the accomplishment of a great quantity of procedures. 2 In contrast, the Northeast region is the one that performs a lesser quantity of procedures, according to the data in this study.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…A study developed with active professionals in the Programa Mais Médicos (PMM) (More Physicians Program) demonstrated that working in the geographic North region is a factor that contributes to the accomplishment of a great quantity of procedures. 2 In contrast, the Northeast region is the one that performs a lesser quantity of procedures, according to the data in this study.…”
Section: Discussionsupporting
confidence: 53%
“…This relation between a expanded scope of practice of physicians and their work in rural and remote areas have been identified in several studies. 2,20,21 Despite that it was not so evident in the nursing professionals, it is suggestive that a nurse who works in a rural unit of a riveside community, with only fluvial access, in Entorno de Manaus, performs more procedures than others interviewed in the same region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations